Modeling the daily dynamics of grass growth of several species according to their functional type, based on soil water and nitrogen dynamics: Gras-Sim model definition, parametrization and evaluation - Kokah, Essomandan Urbain; Knoden, David; Lambert, Richard; Himdi, Hamza; Dumont, Benjamin; Bindelle, Jérôme (Journal of agriculture and food research, 2023)
Gras-Sim model, through the environmental conditions and the dynamics of water and nitrogen in the soil, enables the prediction of the biomass yield in permanent grasslands. It was developed from existing models and simulates the dynamics of several grass species grouped into plant functional types (PFTs) A and B. Model inputs include weather data, fertilizer application, soil data, and cutting management. In contrast to previous models, Gras-Sim proposes a complete nitrogen balance at the field scale as well as a new formalism to estimate actual evapotranspiration based on the crop coefficient (Kc) for a better prediction of biomass production even under moderate stress. Gras-Sim was evaluated in this paper on the basis of data from experiments conducted between 2010 and 2018, on 3 sites fairly representative of the soil and climate conditions in Wallonia (Belgium). The relative root mean square error (RRMSE), normalized deviation (ND), and model efficiency (EF) across all cuts, sites, and PFTs were 29 %, 2 %, and 71 % respectively, for biomass production. Gras-Sim is a simple and efficient model that can be used as a starting point for the design of a decision support tool for better management of permanent grasslands.